[Speakers hand in hand at MultiCultural Center dedication], 1982 (1982)
All of the speakers at the Multicultural Center dedication, standing with their arms crossed and holding the hands of the people next to them. Pictured left to right are: unidentified, David Sanchez, ASI president Dennis Hawk, unidentified, unidentified, President Baker, unidentified, unidentified, History professor Quintard Taylor, unidentified.